The relationship between thyroid peroxidase antibody and differentiated thyroid cancer: a systematic review and meta-analysis - Zhang, Haonan; Tian, Lijun; Wang, Xichang; Shi, Xiaoguang (Frontiers in Endocrinology, 2024)
Background: Thyroglobulin antibody (TgAb) has been found to be associated with the occurrence and development of differentiated thyroid cancer (DTC) for several years, but there is still controversy over whether thyroid peroxidase antibody (TPOAb) is related to differentiated thyroid cancer. Methods: We scrutinized relevant studies published up to July 2023 across four major databases including PubMed, Embase, Cochrane Library, and Web of Science, to examine the association between TPOAb and DTC. Clinical outcome measures include the incidence of DTC, tumor size, extrathyroidal invasion, lymph node metastasis, multifocality, recurrence and bilaterality.Results: 12 original studies were included, involving a total of 20,330 subjects. Our analysis of the included studies revealed that TPOAb+ individuals exhibited a higher risk of developing DTC (OR=1.57 [95% CI: 1.00-2.45], p=0.049) than TPOAb-individuals. Furthermore, TPOAb+ DTC patients were more prone to present with bilateral (OR=1.40 [95% CI: 1.21-1.62], p＜0.00001) and multifocal (OR=1.40 [95% CI: 1.23-1.60], p＜0.00001) tumors than TPOAb-patients. Sensitivity analysis indicated a high sensitivity for these three findings. No significant differences in the risk of extrathyroidal extension and lymph node metastasis, recurrence rate, tumor size, were observed between TPOAb+ and TPOAb-DTC patients.The presence of TPOAb is correlated with an increase prevalence of DTC. However, its effectiveness as a prognostic marker for DTC patients warrants further investigation.